PELATIHAN PENGOLAHAN AIR LIMBAH INDUSTRI RUMAHAN SABLON (WARNA DAN B3) DI KELURAHAN KRENDANG, KECAMATAN TAMBORA, JAKARTA BARAT - Asih Wijayanti; Winarni Winarni; Ratnaningsih Ratnaningsih; Rositayanti Hadisoebroto; Tazkiaturrizki Tazkiaturrizki; Riana Ayu Kusumadewi (Universitas Trisakti, 2020)
The community development conducted is the Training of waste water management (color and hazardous waste) of screen printing home industri in “Krendang Kelurahan”, Tambora District, West Jakarta, which aims to provide training and demonstration to screen printing home industri sothat the liquid waste generated from industrial activities can be handled properly and will not cause environmental problems when discharged into the environment. Waste management is also expected to not butden the business actors about cost and time, so that screen printing businesses are able to do the management themselve. The method used is initial research on the characteristics of screen printing waste, testing in the laboratory in determining the dosage and residence time needed in treating the waste, designing simple processing equipment, training in handling liquid waste printing, and demonstrating the screen printing waste treadment in one of thr screen printing home industri. From the results of laboratory tests and simple installation designs, the optimal conditions for the screen printing waste treadment unit are coagulation and mechanical flocculation units, and preparations unit, witch is carried out in 1 tub with a dose of Alum 45 mg/l.